Proses Rehabilitasi Terhadap Pecandu Narkotika Belum Sepenuhnya Dapat Memulihkan Dari Ketergantungan - Husin Rianda; Ari Azhari (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
Narcotics addicts according to the narcotics law are required to carry out a rehabilitation process in order to save their lives from drug addiction. The rehabilitation is divided into two, namely medical rehabilitation and social rehabilitation. However, even though they have carried out rehabilitation activities, many addicts have not managed to recover. This is due to many factors, such as the substances contained in narcotics, financial factors, human resource factors, family factors, factors within the addict himself and so on. Moreover, narcotics addicts can no longer return to normal as before, that is, when they have not used narcotics. Thus, it is important to provide this information to generation Z so they don't use narcotics. As generation Z is the younger generation who must be protected from the dangers of narcotics. Therefore, the authors carry out community service activities for generation Z in order to provide an understanding of narcotics so that awareness will grow within them to stay away from narcotics. This service uses the seminar method, namely delivery of material, discussion and evaluation. This service was carried out at SMK Negeri 3 Lubuk Linggau. The participants were students and female students. The results of the dedication concluded that the students of SMK Negeri 3 Lubuk Linggau understood that narcotics addicts could carry out rehabilitation to recover from narcotics dependence, but could not recover 100% because the nerves had been damaged. In addition, from the results of the evaluation carried out by the presenters, all participants answered well.